2019
DOI: 10.11002/kjfp.2019.26.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan coating and packaging materials on the quality characteristics of fresh-cut cucumber

Abstract: Minimal processing of fruits into ready-to-eat products is a recent trend which has attracted the attention of consumers (2,3). Currently, fresh-cut fruits are either packaged individually or as mixed fruits with others. Various fruits such as pineapple, watermelon, and apple are commonly sold in the market, but fresh-cut cucumber is yet to gain popularity globally. As the demand for fresh-cut fruits and vegetables is increasing, the shelf life of fresh-cut products is of concern, because their quality deterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…According to the previous reports, the visual quality was preserved by using edible coatings, chemical components such as sodium tripolyphosphate, and antibacterial agents such as nisin, thymol, and tween during the storage period 12 – 22 . Olawuyi and Lee 30 , reported similar results of the visual quality after treating fresh-cut cucumbers with chitosan and other packaging materials. While, Rageh and Abou-Elwafa 31 , reported an increase in the visual quality after treating cucumber with jasmine oil and dry yeast as a spray to prolong the shelf-life.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…According to the previous reports, the visual quality was preserved by using edible coatings, chemical components such as sodium tripolyphosphate, and antibacterial agents such as nisin, thymol, and tween during the storage period 12 – 22 . Olawuyi and Lee 30 , reported similar results of the visual quality after treating fresh-cut cucumbers with chitosan and other packaging materials. While, Rageh and Abou-Elwafa 31 , reported an increase in the visual quality after treating cucumber with jasmine oil and dry yeast as a spray to prolong the shelf-life.…”
Section: Discussionmentioning
confidence: 75%
“…Visual quality assessments were expressed by using 9-point hedonic scale [9 = represents excellent appearance, 7 = represents good, 5 = represents fair, limit of marketability, 3 = represents poor (useable), 1 = represents very poor (unusable)]. Visual quality assessments were applied every 7 days for 21 days 21 , 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Elasticity of the coatings could be increased by addition of glycerol or sorbitol as plasticizer. Chitosan-based film coatings effectively extend the shelf life of carrots [16,17], tomatoes [18], cucumbers [19], bell peppers [20], bananas [21], apples [22], pomegranates [23], pears [24], plums [25], strawberries [26], papaya [27], mango [28], fish [29], meat [30] and minced meat [31,32]. A number of studies concerning coatings composed of chitosan blends with other film-forming biopolymers allowed to keep biodegradability, non-toxicity, compatibility with food products and improve functional properties.…”
Section: Chitosan Applications For Food Shelf Life Prolongationmentioning
confidence: 99%
“…Cucumber's high moisture content, however, presents a challenge for storage, even under refrigeration conditions, because it is susceptible to increased respiration, yellowing, moisture loss, and increased microbial activity, which generates decay, and thus, reduces its shelf life. Thus, it is necessary to protect this fruit with technologies that reduce post-harvest losses [3]. In this regard, significant progress has been made in developing edible nano-coatings [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported that alginate-pectin nanoparticles (NP) prepared by ionic gelation with various essential oils, including LEO, were stable and presented significant antioxidant properties that are beneficial for food preservation [12]. [3] evaluated the quality of fresh-cut cucumbers after coating with chitosan and packaging in various polymer films. They found that a 2% chitosan coating was efficient in maintaining product quality.…”
Section: Introductionmentioning
confidence: 99%